2019
DOI: 10.1002/lno.11338
|View full text |Cite
|
Sign up to set email alerts
|

Giant ice rings on lakes and field observations of lens‐like eddies in the Middle Baikal (2016–2017)

Abstract: Giant ice rings (diameter 5–7 km) detected on lakes Baikal (Russia) and Hovsgol (Mongolia) are a surface manifestation of intrathermocline lens‐like eddies under ice cover. By analyzing satellite imagery, we have detected new ice rings in 2016 and very old ones in 1969 for Lake Baikal. We have also discovered a giant ice ring on a new water body—Lake Teletskoye in the Altai Republic (Russia). Our recent field observations in the Middle Baikal have high temporal and spatial resolution and coverage and include t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
31
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(34 citation statements)
references
References 29 publications
3
31
0
Order By: Relevance
“…The difference in the ice thickness between the background station 1 and the station near the thawed patch at the end of March was 25 cm (inset in Fig.). This is comparable with the difference in the ice thickness between the centre and periphery of the ring structure near Nizhneye Izgolovie Cape (24-32 cm according to Kouraev et al, 2019) as well as the ring structure studied in 2009 near the Kultuk settlement (27-31 cm according to Granin et al, 2015;2018).…”
supporting
confidence: 81%
See 1 more Smart Citation
“…The difference in the ice thickness between the background station 1 and the station near the thawed patch at the end of March was 25 cm (inset in Fig.). This is comparable with the difference in the ice thickness between the centre and periphery of the ring structure near Nizhneye Izgolovie Cape (24-32 cm according to Kouraev et al, 2019) as well as the ring structure studied in 2009 near the Kultuk settlement (27-31 cm according to Granin et al, 2015;2018).…”
supporting
confidence: 81%
“…At this time, a dark area appears in satellite images, where the ice thickness is less than in the surrounding area, and the water level in microcracks is closer to the surface of the ice. An analysis of satellite images indicated more than 50 ice ring formations on Lake Baikal since 1969 (Granin et al, 2015;2018;Kouraev et al, 2016;2019). Study of field research data revealed that ice ring structures form due to circle anticyclonic currents under the ice.…”
mentioning
confidence: 99%
“…Cohen's κ is especially used to measure inter-rater reliability. In the interpretation scheme proposed by Landis and Koch (1977), κ from our validation belongs to the category "substantial agreement". A drawback is that we cannot present a proper validation against ground truth data, as often anticipated in remote sensing studies, but the remoteness of the study area and the potential endangering of human safety largely restricts in situ data collection on-site (see also Sect.…”
Section: Discussionmentioning
confidence: 93%
“…Our approach again utilises the dual-polarisation capability of Sentinel-1 and tests the similarity between classification outcomes of the two polarisation channels using Cohen's kappa score κ (Cohen, 1960). Only if κ was above 0.2 (class "fair agreement" according to Landis and Koch, 1977), was the final classification produced as described above. If κ was below 0.2, all pixels in the image were assigned to the negative class.…”
Section: Classification Of Backscatter Anomalies From Sentinel-1 Datamentioning
confidence: 99%
“…The external morphology of the ring structure has changed significantly to the time of the survey on 11.04.2016 since its first occurrence on 14.04.2016 (dynamics of change in Kouraev et al, 2019). The object was a round-shaped area ~ 7*8 km in size (slightly elongated in the NE direction).…”
mentioning
confidence: 99%